Anti-HEV antibody reactivity rate in voluntary blood donors in China: a Meta-analysis - XU Niuniu; JIAO Zhanying (Zhongguo shuxue zazhi)
[Objective] To explore the relationship between anti-HEV antibody reactivity rate and different age groups in Chinese voluntary blood donors by Meta-analysis. [Methods] Literatures on anti-HEV IgG reactivity rate and anti-HEV IgM reactivity rate of voluntary blood donors in different age groups in China were searched from China National Knowledge Infrastructure (CNKI), PubMed and Wanfang Medicine database, with a search time from January 1, 2007 to December 31, 2023. Risk difference (RD) was selected as the effect size after grouping the included literature according to age, and meta-analysis was performed using Review Manager 5.3 software. [Results] A total of 17 articles were included, among which 16 were about anti-HEV IgG and 15 about anti-HEV IgM. Based on different age grouping methods, they were divided into two groups. The age groups of group A were divided into ≤ 20 years old, 21-30 years old, 31-40 years old, 41-50 years old and >50 years old. The age groups of group B were divided into 18-25 years old, 26-35 years old, 36-45 years old, and ≥46 years old. The pooled results of Meta-analysis showed that the RD value of anti-HEV IgG reactivity rate in group A was 22.92% [95% CI (19.02%, 26.82%)], and the RD value of anti-HEV IgM reactivity rate was 0.67% [95% CI (0.51%, 0.82%)]. The RD value of anti-HEV IgG reactivity rate in group B was 33.03% [95% CI (28.01%, 38.05%)], and the RD value of anti-HEV IgM reactivity rate was 1.13% [95% CI (1.05%, 1.21%)]. The results of subgroup analysis showed that in both group A and B, the anti-HEV IgG reactivity rate in voluntary blood donors increased with age. In group A, no increase in the reactivity rate of anti-HEV IgM with age was found in voluntary blood donors. In group B, the anti-HEV IgM reactivity rate increased with age. Further analysis showed that in the two groups of A and B, the anti-HEV IgM reactivity rate increased with age in areas where the anti-HEV IgM reactivity rate was greater than 1%. [Conclusion] The anti-HEV IgG reactivity rate and anti-HEV IgM reactivity rate in voluntary blood donors increased with age.